Pelatihan Pembuatan Proposal Usaha Sebagai Upaya Mendorong Mahasiswa Mengikuti PKM-K, P2MW dan PMW - Nur Anisa; Rina Yulinar; Nur Aeni; Imam Mahmud (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Entrepreneurship among students plays an important role in reducing the unemployment rate in Indonesia. The Entrepreneurial Student Development Program (P2MW) is one of the government's efforts to increase the entrepreneurial capacity of students. This study aims to evaluate the impact of entrepreneurship training in making business proposals which will be held on September 8, 2024 at Griya Housing, Meneng Indah Building, Bandar Lampung. The methods applied include socialisation, workshops, and evaluations through pre-test and post-test. The results of the study show that 100% of participants now understand the essence of making business proposals, with a high level of satisfaction with the material presented and event management. This training is expected to strengthen the entrepreneurial ecosystem in higher education and encourage active student participation in the world of entrepreneurship.